Diagnostic Utility of Daytime Salivary Melatonin Levels in Smith-Magenis Syndrome - Chik, Constance L. (2010)
An inverted circadian rhythm of melatonin (MT) likely contributes to the sleep disturbance in patients with Smith-Magenis syndrome (SMS). Plasma MT levels have documented this altered rhythm, but daytime levels of salivary MT has not been determined. Daytime measures of salivary MT might have utility in home/outpatient settings for assessing MT levels in undiagnosed patients with clinical features of SMS. The objective of this study was to determine the utility of daytime salivary MT as a diagnostic test in SMS. Thirty individuals with confirmed SMS [28 with del 17p11.2 and 2 with the retinoic acid induced 1 (RAI1) gene mutation] and five controls were studied. Single or serial daytime salivary MT levels were measured. The mean midday salivary MT level was 79.0 pg/ml in SMS patients, compared with 16.3 pg/ml in controls, with nine patients having values similar to controls. The median MT level in SMS patients was 49.0 pg/ml (first and third quartile values = 15.5 and 106.8 pg/ml). Twenty-six (90%) of 29 patients had at least one MT value > 15.5 pg/ml, including 70 (78%) of 90 samples from patients with del 17p11.2 and one (20%) of five samples from the two patients with the RAI1 mutation. Neither the pattern of medication use nor age had an effect on daytime salivary MT levels. Although most SMS patients had elevated daytime salivary MT levels, multiple sampling appears necessary to distinguish patients with SMS from other conditions.